Nietzschean Psychology and Psychotherapy: The New Doctors of the Soul - Wernik, Uri (Lexington Books, 2016)
Friedrich Nietzsche declared himself to be “a psychologist who has not his peer.” Nietzschean Psychology and Psychotherapy: The New Doctors of the Soul illustrates why he was correct and indicates that he was also a soul doctor “who has not his peer.” He is usually unknown to psychologists and treated by philosophers as if he was a philosopher who, as such, wrote about some issues relating to the philosophy of mind. This book acquaints psychologists with Nietzsche and introduces him to philosophers in a new light. It presents Nietzsche’s contributions to psychology, wisdom of life, and psychotherapy dispersed throughout his writings. It hails him the “Overturner,” demonstrating how he overturned many of our notions about love, crime, happiness, morality, language, consciousness, logic, memory, emotions, happiness, and self-actualizing. He is portrayed as the precursor and champion of action-, chance-, and acceptance-oriented self-help and therapy, far from being, as is often claimed, a proponent of depth-, dynamic- or insight-oriented psychotherapy.